Answer:
y = 3x + 4
Explanation:
The first expression represents the linear relationship shown in the table. We can demonstrate this just by replacing each value into the equation, and see if it returns the same values as the table shows.
For
:
![y=3(0)+4=4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/4kxzvqpyvjcessu6674vl2whv367yqfe1s.png)
For
:
![y=3(2)+4=10](https://img.qammunity.org/2020/formulas/mathematics/middle-school/gkhwynvhfild6qeeao3cc4x90l0w0mlhnj.png)
For
:
![y=3(4)+4=16](https://img.qammunity.org/2020/formulas/mathematics/middle-school/dfcctl99xf24k0w9fw444kfysx6po5b3ov.png)
For
:
![y=3(6)+4=22](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vkfdphxordaja99p89wsmwfou3l10gmqqz.png)
As you can see, the first the expression is the only one that completely fits with the table. Therefore, the right answer is the first equation.